2021
DOI: 10.3389/fimmu.2021.752233
|View full text |Cite
|
Sign up to set email alerts
|

Robust Antibody Levels in Both Diabetic and Non-Diabetic Individuals After BNT162b2 mRNA COVID-19 Vaccination

Abstract: The emergence of effective vaccines for COVID-19 has been welcomed by the world with great optimism. Given their increased susceptibility to COVID-19, the question arises whether individuals with type-2 diabetes mellitus (T2DM) and other metabolic conditions can respond effectively to the mRNA-based vaccine. We aimed to evaluate the levels of anti-SARS-CoV-2 IgG and neutralizing antibodies in people with T2DM and/or other metabolic risk factors (hypertension and obesity) compared to those without. This study i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 32 publications
5
78
1
Order By: Relevance
“…That study showed that substantial quantities of neutralizing antibodies were elicited post-vaccination, about five times the seropositivity threshold. However, in contrast to our findings and to the findings by Sourij et al, both SARS-CoV-2 IgG and neutralizing antibodies titers were lower in people with T2DM than people without DM [ 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…That study showed that substantial quantities of neutralizing antibodies were elicited post-vaccination, about five times the seropositivity threshold. However, in contrast to our findings and to the findings by Sourij et al, both SARS-CoV-2 IgG and neutralizing antibodies titers were lower in people with T2DM than people without DM [ 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, people with DM in our study had a mean HbA1c of 51 mmol/mol (6.8%), hence, the differences might be attributed to the different glycemic status of the participants. Similarly, another study examined the levels of anti-SARS-CoV-2 IgG and neutralizing antibodies in people with type 2 DM ( n = 81) and/or other metabolic risk factors (hypertension and obesity) in comparison with those without DM or co-morbidities ( n = 181) [ 7 ]. Antibodies were measured to subjects a minimum of 3 weeks after the second dose of BNT162b2 mRNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most phase 3 clinical trials of SARS-CoV-2 vaccines have not included patients with comorbidities including diabetes; as such, there is a lack of real-world evidence on vaccine side effects and protective effects in this population and the existing data are inconsistent. A study on the antibody levels of diabetic and non-diabetic individuals 3 weeks after immunization with two doses of BNT162b2 mRNA COVID-19 vaccination showed that the neutralizing antibody produced by diabetic patients is 4.42% lower than that of non-diabetic patients [17]. Similarly, a study from Turkey showed that diabetes patients produced lower levels of antibodies four weeks after immunization with two doses of the SARS-CoV-2 vaccine [18].…”
Section: Introductionmentioning
confidence: 99%
“…As diabetes represents an independent risk for disease severity, subjects living with diabetes were included among priority groups for vaccination programmes. Some studies have reported a lower humoral response in diabetic patients after two doses of BNT162b2 [ 37 , 38 ], even if they did not experience a previous exposure to COVID-19.…”
Section: Discussionmentioning
confidence: 99%